1.x2+2x-3≤0 2.x-x2+6<0 3.4x2+4x+1≥0 4.x2-6x-9≤05.4+x-x2<0 6.x2+2x+3<0求不等式解集
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 15:15:31
1.x2+2x-3≤02.x-x2+6<03.4x2+4x+1≥04.x2-6x-9≤05.4+x-x2<06.x2+2x+3<0求不等式解集1.x2+2x-3≤02.x-x2+6<03.4x2+4x
1.x2+2x-3≤0 2.x-x2+6<0 3.4x2+4x+1≥0 4.x2-6x-9≤05.4+x-x2<0 6.x2+2x+3<0求不等式解集
1.x2+2x-3≤0 2.x-x2+6<0 3.4x2+4x+1≥0 4.x2-6x-9≤05.4+x-x2<0 6.x2+2x+3<0求不等式解集
1.x2+2x-3≤0 2.x-x2+6<0 3.4x2+4x+1≥0 4.x2-6x-9≤05.4+x-x2<0 6.x2+2x+3<0求不等式解集
x^2+2x-3
1111
(x-x2)(x2+x-6)分之(x2+3x)(x2-3x+2)
1.x2+2x-3≤0 2.x-x2+6<0 3.4x2+4x+1≥0 4.x2-6x-9≤05.4+x-x2<0 6.x2+2x+3<0求不等式解集
(x2-3x)2-x(x2-3x)-2x2
x2-3x≥0,x2-x-6<0,x2-x+5≤0,2x2+3x+2>0 的解是什么?x2-3x≥0,x2-x-6<0,x2-x+5≤0,2x2+3x+2>0 的解是什么?
约分x2+x-2/x2-x-6
(x2-x)2+6(x2-x)+9
计算:x2-5x+6/x2-4x+3 + x2-4x+3/x2-2x+1 + x2-3x-4/1-x2
(x2+2x-3)(x2+2x+4)+6因式分解
不等式x2+2x-3/-x2+x+6
已知x2 3x-2=0,求2x-4╱x2 6x 9÷(x-3)×x2-9╱2x-x2的值
已知x2-4x+1=0,求x2/(x2)2-3x2+1
几道数学题,解不等式X2-4X-5≤0-2X2+3X-2<0-X2+8X-3>04X2-18X+81/4>01/2X2-3X+5<03X2-2X+1<0X2+2X-3≤0X-X2+6<04X2+4X+1≥0-4+X-X2<03X2-4<02X-X2≥-14-X2≤0(X-A)(X-2)<0
1.x^2-3x-18=0 2.x^2+3x-5=0 3.x^2-4x-7=0 4.3^2-6x-9=0 5.3x^2-6x-9=0不解方程求:x1+x2=...x1乘以x2=...1/x1+1/x2=...x1^2+x2^2=...(x1-x2)^2=.
解分式方程:1/(x2-2x-3) +2/(x2-x-6) +3/(x2+3x+2)=0
解分式方程:1/(x2-2x-3) +2/(x2-x-6) +3/(x2+3x+2)=0
解方程:1/x2+x +1/x2+3x+2 +1/x2+5x+6 +1/x2+7x+12 +1/x2+9x+20=5/x2+11x-708解方程:1/x2+x +1/x2+3x+2 +1/x2+5x+6 +1/x2+7x+12 +1/x2+9x+20=5/x2+11x-708
x2+2x-3≤0
x2-2x-3≤0